Psychological Burden Faced by Parents having Children with Thalassemia in a Teaching Hospital of Birgunj, Madhesh province - Shrestha, Romina; Shah, Rubi; Bhandari, Keshav; Banstola, Ratna Shila (Journal of Institute of Medicine Nepal, 2024)
Introduction Caring for a child suffering from thalassemia is very stressful for parents. The study was aimed to identify the psychological burden of parents having children with thalassemia. Methods Cross-sectional analytical study was done. The parents having children diagnosed with thalassemia and receiving service from Pediatric OPD, National Medical College were the study participants. Non-probability convenience sampling technique was used and sample size was 88. Data was collected through face-to-face interviews using a structured interview schedule. Data analysis was done in SPSS version 16. Chi-square test, fisher’s exact test and odds ratio were used to examine the association. Results Mean psychological burden score was 47.47 ± 10.9, and 71.6% of parents had moderate level of psychological burden. Level of psychological burden was associated with parents’ sex (p=0.03), education level (p=0.03), and income (p=0.01). Odds ratio determined that psychological burden was 2.9 times higher (95% CI = 1.1-7.6) among mothers, 3.7 times higher (95% CI = 1.4-9.9) for the parents whose income was insufficient to get their needs met. Non-literate parents were 3.6 times and parents with primary to secondary level education were 1.6 times more likely to have psychological burden. In contrast, those with higher secondary or above levels of education were less likely to perceive psychological burden (OR = 0.3, 95% CI = 0.4-1.0). Conclusion More than two-thirds of the parents having children with thalassemia tend to have moderate levels of psychological burden. The measures to reduce psychological burden of parents should focus more towards mothers, those parents with low education level and with less income.